KONSEP DIGITAL MARKETING USAHA MIKRO KECIL DAN MENENGAH (UMKM) : PENGAMBANGAN DAN STRATEGI - Rakhman, Muhammad Arif (Program Studi Ekonomi Syariah, 2024)
Micro, Small and Medium Enterprises (MSMEs) are the largest economic actors in the Indonesian economy, MSMEs also have a very large role in economic development and growth, especially in Indonesia. One of the developments and strategies that can be carried out to develop MSMEs is through development and marketing strategies using digital marketing methods. This research design uses a qualitative research method with a descriptive approach based on the results of observations and documentation studies. The object of this research is MSME owners in Ambarawa District, Semarang Regency, Central Java Province which consists of 10 MSMEs but only 8 samples answered the survey and 5 were eligible according to the category to make video calls for interviews. The results of this research are that the concept of developing digital marketing has become an opportunity for MSMEs in the district. Ambarawa District. Semarang especially in terms of sales has increased, but there are several MSMEs that still market their businesses traditionally due to limited knowledge and lack of human resources and in the future they will still be in the process of being able to develop their businesses based on digital marketing. The strategy carried out by small MSME players. Ambarawa District. Semarang has done this optimally through several strategies, including strengthening the Digital Business Brand name, creating discount programs, utilizing Social Media, Registering MSME products on online marketing platforms (e-commerce), including reviews or testimonials and placing Paid Advertisements.